Sediment Provenance and Distribution on the Northwest African Continental Shelf - Hasnaa Nait-Hammou; Khalid El Khalidi; Otmane Khalfaoui; Ahmed Makaoui; Melissa Chierici; Chaimaa Jamal; Mohammed Idrissi; Bendahhou Zourarah (Journal of Marine Science and Engineering)
This study analyzes the mineralogical and geochemical composition of 38 surface sediment samples from the northwest African continental shelf between Cap Boujdour (26.5° N) and Cap Blanc (20.5° N). Using a multiproxy approach, sediment characteristics were assessed through grain size, calcium carbonate (CaCO3), and organic carbon (Corg) measurements, along with X-ray diffraction (XRD) and X-ray fluorescence (XRF) for geochemical analysis. Bottom water properties, including temperature, salinity, and dissolved oxygen, were measured at various stations using a Conductivity, Temperature, and Depth (CTD) sensor. The results reveal that the inner shelf sediments are primarily mud, with high concentrations of terrigenous elements such as iron (Fe), silicon (Si), rubidium (Rb), and potassium (K), with Fe and Si concentrations ranging from 2.1 to 4.3 wt%. The middle and outer shelf sediments are dominated by biogenic carbonates, with CaCO3 levels approaching 65%, and elevated calcium (Ca) and strontium (Sr) content. These areas also exhibit the highest bottom water temperatures (up to 16 °C), salinity (36%), and moderate oxygen levels (2–4 mL/L). Slope sediments are enriched with mud and montmorillonite, and aeolian contributions are more pronounced south of Dakhla, as indicated by elevated quartz levels (up to 20%) and the presence of illite, aluminum oxide (Al2O3), and iron oxide (Fe2O3). This study provides valuable new insights into sedimentary processes on the northwest African shelf, offering implications for regional environmental management and resource exploration.